2000
DOI: 10.1074/jbc.m003504200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Cytosolic Prostaglandin E2 Synthase That Is Functionally Coupled with Cyclooxygenase-1 in Immediate Prostaglandin E2Biosynthesis

Abstract: Here we report the molecular identification of cytosolic glutathione (GSH)-dependent prostaglandin (PG) E 2 synthase (cPGES), a terminal enzyme of the cyclooxygenase (COX)-1-mediated PGE 2 biosynthetic pathway. GSHdependent PGES activity in the cytosol of rat brains, but not of other tissues, increased 3-fold after lipopolysaccharide (LPS) challenge. Peptide microsequencing of purified enzyme revealed that it was identical to p23, which is reportedly the weakly bound component of the steroid hormone receptor/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
527
2
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 649 publications
(558 citation statements)
references
References 41 publications
(54 reference statements)
20
527
2
5
Order By: Relevance
“…[35][36][37] Expression of mPGES1 is markedly induced by pro-inflammatory stimulation in various tissues. 35 PGES1 is involved in the COX-2-mediated PGE2-biosynthetic pathway 35 ; mPGES2 is abundant in brain, heart, skeletal muscle, kidney, and liver 37 ; cPGES is distributed ubiquitously in the cytosol of various cells 36 ; and COX-1 contributes to PGE2 generation by PGES2 and cPGES.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37] Expression of mPGES1 is markedly induced by pro-inflammatory stimulation in various tissues. 35 PGES1 is involved in the COX-2-mediated PGE2-biosynthetic pathway 35 ; mPGES2 is abundant in brain, heart, skeletal muscle, kidney, and liver 37 ; cPGES is distributed ubiquitously in the cytosol of various cells 36 ; and COX-1 contributes to PGE2 generation by PGES2 and cPGES.…”
Section: Discussionmentioning
confidence: 99%
“…35 PGES1 is involved in the COX-2-mediated PGE2-biosynthetic pathway 35 ; mPGES2 is abundant in brain, heart, skeletal muscle, kidney, and liver 37 ; cPGES is distributed ubiquitously in the cytosol of various cells 36 ; and COX-1 contributes to PGE2 generation by PGES2 and cPGES. 36,39,40 We immunohistochemically confirmed the presence of mPGES1 in primary basophils, but we were unable to assess the protein expression of the other PGES enzymes, because antibodies against mPGES2 and cPGES were not available in our laboratory. Nevertheless, transcripts encoding mPGES1, mPGES2, and cPGES were all detected in BMBAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the inducible mPGES-1, another mPGES (mPGES-2) is constitutively expressed in many cells without any further induction during inflammation (7). In addition, a cytosolic protein possessing PGES activity (cPGES) has been characterized and found to be constitutively expressed in various cells (8). Cytosolic PGES is not generally induced by proinflammatory stimuli except in the brain, where a minor increase has been reported (8).…”
mentioning
confidence: 99%
“…In addition, a cytosolic protein possessing PGES activity (cPGES) has been characterized and found to be constitutively expressed in various cells (8). Cytosolic PGES is not generally induced by proinflammatory stimuli except in the brain, where a minor increase has been reported (8). It has been demonstrated that mPGES-1 functionally uses PGH 2 generated by COX-2 (5,6), but some evidence also exists for a role of COX-1 (9).…”
mentioning
confidence: 99%